(untitled) (Rudarsko-geološko-naftni zbornik, 2017)
The MSW generation models are important elements of the waste management planning. This paper gives the findings of the second part of the research on Croatian MSW generation mechanism. The correlations of 17 variables are shown. The relationships between the variables are discussed. In the conclusion, independent variables to be hypothesised and tested in a model for the next part of the research are proposed.